Differences of Weighted Mixed Symmetric Means and Related Results. (18th October 2010) - Khan, Khuram Ali; Pečarić, J.; Perić, I.
Abstract : Some improvements of classical Jensen's inequality are used to define the weighted mixed symmetric means. Exponential convexity and mean value theorems are proved for the differences of these improved inequalities. Related Cauchy means are also defined, and their monotonicity is established as an application.